Body mass index trajectories among children aged 0 - 6 years in Yanbian Korean Autonomous Prefecture, 2019: a lambda-mu-sigma analysis of physical examination data - Ping LI; Miao ZHENG; Meihua JIN (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo establish variation trajectories and reference values of body mass index (BMI) for 0 - 6 year old children in Yanbian Korean Autonomous Prefecture (Yanbian) using the lambda-mu-sigma (LMS) method, and to analyze disparities between the BMI of local children and those of national references to evaluate the growth and development of children in the Yanbian region. MethodsUsing stratified random cluster sampling, we collected data from 6 650 children aged 0 - 6 years (1 557/1 860 and 1 356/1 859 Korean/Han boys and girls) who received a physical examination at five community health centers in five counties/prefectures in Yanbian region in September 2019. Simultaneous modeling of mean (mu), coefficient of variation (sigma), and skewness (lambda) of the children's BMI was performed using the LMS method to calculate percentiles 3, 25, 50, 75, 97 of age-specific reference BMI values.ResultsVariations in BMI showed a similar trend with age among the boys and girls surveyed. There were significant gender differences in age-specific BMI values, with boys having higher mean BMIs than girls at 3 months (17.43 ± 1.53 vs. 16.77 ± 1.48), 6 months (17.89 ± 1.73 vs. 17.35 ± 1.62), 1 year (17.10 ± 1.44 vs. 16.72 ± 1.32), 1.5 years (16.53 ± 1.31 vs. 15.94 ± 1.26), 2 years (16.46 ± 1. 45 vs. 16.10 ± 1.50), 2.5 years (16.26 ± 1.32 vs. 15.73 ± 1.44), 3.5 years (16.11 ± 1.62 vs. 15.66 ± 1.69), 4.5 years (15.80 ± 1.74 vs. 15.51 ± 1. 70), 5 years (16.03 ± 2.10 vs. 15.54 ± 1.83), 5.5 years (16.44 ± 2.55 vs. 15.69 ± 1.86), and 6 years (16.77 ± 2.88 vs. 16.07 ± 2.76), respectively (all P < 0.05). The participants' BMI growth trajectories derived from the LMS analysis showed that for the surveyed boys between one month and one year of age and girls between one month and 1.5 years of age, all percentile values of age-specific BMI were lower than those of the national reference values; but for the surveyed boys older than one year of age and girls older than 1.5 years of age, all the percentile values of age-specific BMI of were higher than those of the national reference values, except for the percentile 3 values, which were lower than those of the national reference values. ConclusionFor the children aged 0 - 6 years in Yanbian region, the BMI values of boys are generally higher than those of girls and the overall BMI values of the children have exceeded the national reference values.